Subcutaneous Leiomyosarcoma of the Frenulum - D. Mendis; S. R. J. Bott; J. H. Davies (The Scientific World Journal)
Leiomyosarcomas of the penis are rare, with only 29 reported cases to date. We record the case of a patient who presented with a 2-year history of a seemingly indolent penile skin lesion. On histopathology of the local resection, a diagnosis of subcutaneous leiomyosarcoma was made. Specifically, leiomyosarcoma of the penile frenulum has not been clearly reported previously. The patient underwent a further excision to ensure an adequate resection margin and has had no disease recurrence at subsequent follow-up. Our case was of a lesion that, although clinically benign, was malignant and this possibility should be borne in mind when assessing patients.